Respons Pertumbuhan Bibit Talas (Colocasia Esculenta L.) terhadap Berbagai Komposisi Media Tanam dan Dosis Pupuk NPK - Sendry Putri Andani; Jonatan Ginting; Yaya Hasanah (Jurnal Agroekoteknologi, 2018)
ABSTRACT   Taro tuber is one of the few commodities tubers that can be used as an alternative source of food other besides rice that is both healthy and safety. Cultivating of taro and increase production to do some of them use the alternative media composition suitable cropping and NPK fertilizer. This research was conducted in Jalan Klambir Lima Kecamatan Sunggal, Medan, with altitude ± 25 meters above sea surface began  from April to Juli 2016. This research used factorial randomized block design with two factors. The first factor was growing media composition (top soil (control)); top soil : sand (1:1)); top soil : sand : empty bunches of palm oil compost (1 : 1: 1)); top soil : sand : empty bunches of palm oil compost (2: 1 : 1)); top soil : sand : empty bunches of palm oil compost (3: 1: 1)) and the second factor is doses of NPK fertilizer (0; 2; 4; 6 g/polibag). Parameter observed was plant height, total leaf area, plant fresh weight, shoot dry weight, and  root dry weight. The result of this research showed that growing media composition were significantly effect to plant height parameter 2 week after planting, total leaf area, plant fresh weight, shoot dry weight, root dry weight, and ratio of shoot and root. doses of NPK fertilizer composition were significantly effect to total leaf area parameter, plant fresh weight, and shoot dry weight. Interaction of growing media composition and dose of NPK fertilizer were significantly effect to plant height 2-9 week after planting and plant fresh weight. Keywords : growing media, NPK fertilizer, taro